(a-2b)的平方-14(a-2b)+49
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/06 11:54:20
(a-2b)的平方-14(a-2b)+49(a-2b)的平方-14(a-2b)+49(a-2b)的平方-14(a-2b)+49(a-2b)的平方-14(a-2b)+49=(a-2b-7)²(
(a-2b)的平方-14(a-2b)+49
(a-2b)的平方-14(a-2b)+49
(a-2b)的平方-14(a-2b)+49
(a-2b)的平方-14(a-2b)+49
=(a-2b-7)²
(a-2b)^2-14(a-2b)+49
=(a-2b-7)^2
(a+2b)的平方-4(a-b)的平方
已知:a的平方+9b的平方+4a=12b-8求(a+b)(a-b)-(a+b)的平方-2(a-b)的平方
合并同类项3(a-b)的平方+(a+b)-2(a+b)-(a-b)的平方-4(a+b).
化简(2A+B)的平方-4A(A+B)
4a(a+b)-(2a+b)的平方 得数
计算(a-2b)的平方-a(a-4b)
a的4次方+b的4次方=a平方-2a平方b平方+b平方.求a的平方+b的平方和a+b
已知4a平方-3b平方=7 3a平方+2b的平方=15 求14a平方-2b平方的值
已知4a平方-3b平方=7 3a平方+2b的平方=19 求14a平方-2b平方的值
a平方-4b平方-a+2
(a+2b)的平方-4b的平方
已知a的平方+b的平方-2a+4b+5 ,求a的平方+2ab+b的平方分之a的平方-b的平方
4(a的平方b-2ab平方)-(a平方b+2ab平方)
4(a的平方b-2ab平方)-(a平方b+2ab平方)?
a的平方b-(-3ab平方)+(-4a平方b)-2ab平方=
4b的平方(2a-b)+a的平方(b-2a)
(a+2b)(a-2b)(a的平方+4b的平方)
(a+2b)(3a-6b)(a的平方+4b的平方) 急